Legal status of a municipality as a corporation in Canadian law - A. Larichev (Правоприменение)
УДК 342.25The purpose of this article is to study the legal status of a municipality as a corporation in Canadian law.The methods of theoretical analysis, along with legal methods, including formal-legal method are used to achieve this goal.Results. In the article the author notes the difficulties in determining the legal nature of a municipal corporation in legal research. In literature, there exists an approach to the corresponding subject as both a public corporation, differentiating from the entrepreneurial form (J. Dillon, E.A. Sukhanov), as well as the dual approach, which allows for the double, private-public character of its legal nature (I. Rogers).As the author maintains, a municipal corporation in Canadian law can be defined as a form of a statutory corporation of a special kind, the legal personality of which, unlike one of the common law corporations, is limited by normative legal acts (statutes) of general or individual character.Despite the existence of general theoretical framework of legal design of a municipal corporation, legislators of Canadian provinces differ in determination of its elements. Among the most common elements to be identified is the population, but in some cases the legislation also indicates the territory and local government bodies.The form of a statutory corporation also presupposes the definition in the legislation of a clear goal (goals) for its creation. At the same time, as noted in the article, the tendency of the recent time is a departure from specifying concrete goals in favor of more general formulations.Conclusions. This tendency, together with other separate measures to liberalize the legal status of municipal corporations (for example, giving municipalities the status of natural person), without reconsidering the fundamental foundations of their legal nature, indicatesa virtual erosion of the approach to the status of a municipality as a statutory corporation, as well as the need for both theoretical and normative work in order to eliminate the corresponding defects and contradictions.